The Influence of Service Quality, Customer Relations and Product Quality on Intention to Return to The Bensara Café Through Customer Satisfaction as Mediation - Daris Rahadian Purnawan; Andyan Pradipta Utama; Tine Yuliantini; Alvita Sari (Dinasti Publisher, 2024)
This study aims to analyze the influence of service quality, customer relationship, and product quality on revisit intention at The Bènsara Cafe, with customer satisfaction as a mediating variable. Coffee has become an important part of many people's daily lives, with Indonesia being one of the largest coffee producers in the world. The increase in coffee consumption has driven rapid growth in coffee shops, including in South Jakarta. The research method used is quantitative with a total of 170 respondents from the DKI Jakarta area, who have purchased at least once at The Bènsara Cafe. Data analysis was conducted using Smart PLS 3. The results show that service quality has a positive and significant effect on revisit intention. Customer relationship does not have a significant effect on revisit intention. Product quality has a positive and significant effect on revisit intention. Customer satisfaction also has a positive and significant effect on revisit intention. However, service quality, customer relationship, and product quality do not have a significant effect on revisit intention through customer satisfaction as a mediating variable. The theoretical contribution of this research is to provide insights into the influence of service quality, customer relationship, and product quality on revisit intention with customer satisfaction as a mediating variable. Practically, this study provides strategic recommendations for the owners of The Bènsara Cafe to improve service and product quality to increase customer revisit intention.